2010
DOI: 10.1152/ajpheart.00652.2009
|View full text |Cite
|
Sign up to set email alerts
|

Prelesional arterial endothelial phenotypes in hypercholesterolemia: universal ABCA1 upregulation contrasts with region-specific gene expression in vivo

Abstract: Atherosclerosis originates as focal arterial lesions having a predictable distribution to regions of bifurcations, branches, and inner curvatures where blood flow characteristics are complex. Distinct endothelial phenotypes correlate with regional hemodynamics. We propose that systemic risk factors modify regional endothelial phenotype to influence focal susceptibility to atherosclerosis. Transcript profiles of freshly isolated endothelial cells from three atherosusceptible and three atheroprotected arterial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Among these genes are some that have been described previously as playing a role in the atherosclerotic endothelium, particularly Abca1 . This gene has been identified as upregulated in the swine endothelium in response to a brief hypercholesterolemic diet, 7 a finding that is consistent with its regulation in our ApoE −/− hyperlipidemic and acute hyperlipidemic mice. The protein encoded by Abca1 has been shown to modulate the transport of phospholipids and cholesterol to apo AI through the endothelial layer and is atheroprotective in vascular ECs because of this role in cholesterol efflux.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Among these genes are some that have been described previously as playing a role in the atherosclerotic endothelium, particularly Abca1 . This gene has been identified as upregulated in the swine endothelium in response to a brief hypercholesterolemic diet, 7 a finding that is consistent with its regulation in our ApoE −/− hyperlipidemic and acute hyperlipidemic mice. The protein encoded by Abca1 has been shown to modulate the transport of phospholipids and cholesterol to apo AI through the endothelial layer and is atheroprotective in vascular ECs because of this role in cholesterol efflux.…”
Section: Discussionsupporting
confidence: 86%
“…Similar studies on ECs isolated from swine maintained on a brief hypercholesterolemic diet supported these findings and reported an upregulation of ABCA1 in response to diet across all regions tested. 7 Although swine is a useful model of human atherosclerosis and its size allows for successful in vivo endothelial expression studies, there are significant limitations for their use in genetic studies. Although the small size of the mouse aorta does not allow for the spatial resolution achieved in swine, inbred mouse strains allow for genetic manipulation, biological replicates, and more high-throughput approaches.…”
mentioning
confidence: 99%
“…We found that the LAD, a classically "atheroprone" coronary artery in adulthood (2,18), is more susceptible to transcriptional alterations as a result of juvenile obesity, compared with the more "atheroresistant" descending thoracic aorta (17). Notably, we identified a number of genes in the LAD (e.g., ACP5, LYZ, CXCL14, APOE, PLA2G7, LGALS3, SPP1, ITGB2, CYBB, P2RY12) that are implicated in atherosclerosis based on published literature (1, 10, 22-24, 27, 32, 33, 45, 48, 51, 56, 64, 74, 77, 84) and whose expression was markedly upregulated with juvenile obesity.…”
Section: Discussionmentioning
confidence: 80%
“…Because it is well established that coronary arteries, particularly the LAD, are highly susceptible to atherosclerosis (2,18) relative to other vascular beds such as the descending thoracic aorta (17), the changes in vascular gene expression produced by juvenile obesity that are exclusive to the LAD are of particular interest. In this regard, a number of genes found to be markedly upregulated in the LAD of obese pigs are implicated in the progression of atherosclerosis, including ACP5, LYZ, CXCL14, APOE, PLA2G7, LGALS3, SPP1, ITGB2, CYBB, and P2RY12 (Table 3) (1, 10, 22-24, 27, 32, 33, 45, 48, 51, 56, 64, 74, 77, 84).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the atheroprotective flow patterns should induce liver X receptors and hence up-regulate ABCA1 to facilitate reverse cholesterol transport 35 . Civelek et al reported no site-specific differences in endothelial ABCA1 expression between susceptible and protected sites of swine arteries 36 . However, our published work showed that ABCA1 level is lower in the mouse aortic arch compared with thoracic aorta 35 .…”
Section: Discussionmentioning
confidence: 96%